Rapid Response to Ready RNs for the COVID-19 Pandemic. Issue 4 (July 2021) - Hessler, Karen L.; Haylett, Wendy J.; Becker, Maude; Voss, Jennifer; Waterman, Kari; Higgins, Jennifer; Kidin, Lisa; Villavicencio, Diane; DelMonte, JoAnn
Abstract : Rapid response is a common term in hospital settings, reflecting immediate clinical response to a critical challenge. In preparation for the oncoming pandemic of novel coronavirus 2019, nurse leaders within a large health system in the Mountain West region implemented a rapid response to prepare nondirect care registered nurses for deployment to the bedside. This article highlights the prompt action, organization, and implementation of this process, as well as the lessons learned for future events.